2002
DOI: 10.1046/j.1365-2141.2002.03937.x
|View full text |Cite
|
Sign up to set email alerts
|

A study on 289 consecutive Korean patients with acute leukaemias revealed fluorescence in situ hybridization detects the MLL translocation without cytogenetic evidence both initially and during follow‐up

Abstract: Summary. Translocations involving the MLL gene on the chromosome 11 (11q23) are frequently observed in acute leukaemia. The detection of this genetic change has a unique significance as a result of its implication of poor prognosis. To reveal the utility of fluorescence in situ hybridization (FISH) in detecting the MLL translocation, we analysed 289 consecutive Korean patients (children and adults) with acute leukaemias using both conventional cytogenetic analysis (CC) and FISH, placing an emphasis on the resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
15
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 26 publications
2
15
0
Order By: Relevance
“…The centromeric signals serve as internal control to rule out increased number of gene signals due to polysomy. The expanding application of molecular cytogenetic technique has rendered amplification of such genes as MYC, MLL, and AML1 more readily detectable [12][13][14][15]. The cases hitherto reported on gene amplification in hematologic malignancies mostly involved acute myeloid leukemia (AML), and CMYC appears to be the most frequently amplified gene in AML.…”
Section: Discussionmentioning
confidence: 99%
“…The centromeric signals serve as internal control to rule out increased number of gene signals due to polysomy. The expanding application of molecular cytogenetic technique has rendered amplification of such genes as MYC, MLL, and AML1 more readily detectable [12][13][14][15]. The cases hitherto reported on gene amplification in hematologic malignancies mostly involved acute myeloid leukemia (AML), and CMYC appears to be the most frequently amplified gene in AML.…”
Section: Discussionmentioning
confidence: 99%
“…1 So far, 13 cases have been reported in the literature, 11 in acute myeloid leukemia (AML) patients [1][2][3][4][5][6][7][8] and 2 in B-cell precursor acute lymphoblastic leukemia (ALL). 9 It was also recently reported that MLL is fused to TET1 in only 5 out of 1,590 MLL rearranged AML cases (0.3%).…”
mentioning
confidence: 99%
“…As proposed by Lee et al, we confirm the need to collect and report more cases and to test the leukemogenic activity of MLL-TET1 associated to demethylating agents in a murine bone marrow transduction/transplantation model system. Antoine Ittel, 1,2,3 Eric Jeandidier, 3,4 Catherine Helias, 1,3 Nathalie Perrusson, 2 Catherine Humbrecht, 4 Bruno Lioure, 5 Isabelle Mazurier, 6 Caroline Mayeur-Rousse, 1 Amandine Lavaux, 3,4 Sylvie Thiebault, 8 Felix Lerintiu, 9 Carine Gervais, 1,3 …”
mentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11] There has been little research into the common features of MLL-TET1 rearrangements. Here we provide information about molecular and clinical characterization of MLL-TET1 rearrangements diagnosed in 3 AML patients.…”
mentioning
confidence: 99%
“…We summarized the published data to evaluate patients' characteristics (Table 2). [4][5][6][7][8][9][10][11] A molecular characterization at the genomic or transcript level was performed only for a subset of patients. Eight of 11 AML patients (72.7%) were classified as FAB-M4/M5 subtypes; 7 men and 5 women with a median age of 38.0 years (range 1 month to 67 years).…”
mentioning
confidence: 99%